STRATEGI PEMBELAJARAN GURU DALAM MENGELOLA AMARAH SISWA (STUDI KASUS DI KB ANGGREK MUARA BADAK TAHUN AJARAN 2015/2016 - Nurintang -; Rizqi Syafrina (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2018)
Early children who control their emotions well, in general will be accepted by the environment well too. Conversely, angry students will be very detrimental to other students because a lot of science that should get ignored.by that's why a strategy used by teachers in managing anger of children is very determine the outcome of teaching and learning process. This study aims to find out the Teacher Learning Strategy in Managing Student Angarah Group B in the Anggrek Muara Badak Playing Group of Learning Year 2015/2016. In this study the approach used is qualitative descriptive method approach that is research that intends to understand the phenomenon about what experienced research subjects. The subjects were sixteen students, consisting of five boys and eleven girls. Data collection in this study using observation sheet, Interview Sheet, and Documentation. Data analysis techniques used in this study are Miles and Hiberman techniques that include data collection (data collection); data reduction; presentation of data (data display); and conclusion or verification (conclution drawing & verifying). From the results of research that has been done revealed that the Teacher Learning Strategy in Managing Student Angarah on Group B in the Clock Play Anggrek Estuary Rhino Year Learning 2015/2016 refers to the three important elements of emotional intelligence; (1) Personal skills (self-managing); (2) social skills (dealing with a relationship); (3) social skills (intelligence to arouse the desired response to others). While the cause of students become angry is: (1) because Lack of attention, too mendekti, have a brother who was not far adrift until the pattern of parenting that tends to side with one child. (2) Although there is a single child who is angry but it happens because the parenting pattern of parents who tend to spoil the child too.